The encyclopedia of golf - Campbell, Malcolm 1944- (Dorling Kindersley, 1994)
This encyclopaedia of golf covers all the major aspects of the game, containing a "walk-the-course artwork" of every major championship course. It contains facts, stories and memorabilia that highlight the careers of those that have made significant contributions to the game.